Intercultural Mediation in “La Tola”: The Political Action and the Cultural Rights of the Publics in Artistic Practices - Rosero Delgado, Gabriela; Sánchez Cárdenas, Ricardo; Tituaña, Samuel (Journal Studies of Public Policy, 2024)
The relevance of socio-historical analysis in Ecuador’s cultural policies lies in the operationalization of concepts such as (inter)cultural rights, the "return of the state" in the face of neoliberal hegemony, and the vindication of the right to free time as the foundation of any artistic or cultural mediation. Based on the artistic practices and (inter)cultural mediations developed in a university extension project in the historic neighborhood of "La Tola" in Quito, this study presents methodological strategies and theoretical reflections on the tradition of cultural mediation in Latin America. Interdisciplinary research into inequalities and the social conflicts stemming from the socio-cultural legacy of neoliberalism and neocolonialism is crucial for conceiving cultural rights and policies at various levels of analysis: from public-state dimensions, both national and local, to community-level approaches, which are essential to addressing the global-transnational issue of the commons.